2019
DOI: 10.3390/medicina55070372
|View full text |Cite
|
Sign up to set email alerts
|

Is Scientific Medical Literature Related to Endometriosis Treatment Evidence-Based? A Systematic Review on Methodological Quality of Randomized Clinical Trials

Abstract: Background and objectives: Informed decision-making requires the ability to identify and integrate high-quality scientific evidence in daily practice. We aimed to assess whether randomized controlled trials (RCTs) on endometriosis therapy follow methodological criteria corresponding to the RCTs’ specific level in the hierarchy of evidence in such details to allow the reproduction and replication of the study. Materials and Methods: Using the keywords “therapy” and “endometriosis” and “efficacy” three bibliogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Clinical trials are financed and carried out overwhelmingly by them, sometimes at the request of national agencies such as the Food and Drug Administration in the USA. It is in this political-industrial movement that evidence-based medicine and its statistical methods of randomization have been established, giving the illusion of a mathematical demonstration that cannot be falsified (Capraş et al., 2019). 1 The principle is to substitute statistical calculation for clinical experience, mathematical demonstration for medical practice.…”
Section: Big Pharma’s Influence On Medical Knowledge Productionmentioning
confidence: 99%
“…Clinical trials are financed and carried out overwhelmingly by them, sometimes at the request of national agencies such as the Food and Drug Administration in the USA. It is in this political-industrial movement that evidence-based medicine and its statistical methods of randomization have been established, giving the illusion of a mathematical demonstration that cannot be falsified (Capraş et al., 2019). 1 The principle is to substitute statistical calculation for clinical experience, mathematical demonstration for medical practice.…”
Section: Big Pharma’s Influence On Medical Knowledge Productionmentioning
confidence: 99%
“…Endometriosis treatment remains one of the most controversial topics in gynecology, due in part to a lack of knowledge about the pathogenesis and natural history of endometriosis, as well as limited highquality data to guide individual care. 34 Medical management is often used to treat the symptom of dysmenorrhea, but surgery is necessary to definitely diagnose the disease, and can also improve symptoms. 10,35 Our study found that all sequential medical then surgical treatment pathways are cost effective in the treatment of endometriosis when compared with proceeding immediately to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are serious limitations in the interpretation of clinical trials. 8 Accordingly, evidence on the best therapeutic regimens has not yet been established. 9 Other clinical options exist, but the cost, side effects, and similarity of results compared with hormonal contraceptives give them limited utility.…”
mentioning
confidence: 99%